The influence of reward, work-life balance on employee retention: The mediating effect of Job satisfaction Generation Z employees in West Kalimantan - Syal, Adrian; Rosnani, Titik; Daud, Ilzar; Kalis, Maria Christiana Iman; Hendri, M. Irfani (Institute of Computer Science (IOCS), 2024)
Generation Z is a generation that is dominating the working world at this time, Generation Z is known as a generation that shows low loyalty and retention. Some studies prove that Gen Z tends to leave the company because they feel dissatisfied with the job and want to explore their career. This study examines and analyzes the relationship and influence between rewards and work-life balance on employee retention with job satisfaction as a mediating relationship. The type of research is explanatory quantitative research, this research was developed using structural equation modeling (SEM) and its implementation using AMOS 24. The population in this study were generation Z employees in private trade organizations in West Kalimantan. A total of 219 people were sampled by the purposive sampling method with the following criteria: Employees working in private organisations in the field of trade in West Kalimantan, minimum age criteria of 18-26 years with a working period of more than 6 months in West Kalimantan. The results of the study supported the hypothesis that was constructed by stating that there is an influence between the independent variable, mediating variable and the dependent variable. This study found that rewards and work-life balance have a positive and significant effect on employee retention and job satisfaction of the employees. The research also shows that job satisfaction is able to significantly mediate between either rewards or work-life balance on employee retention.